Collaboration in development between U.S. foundations and African universities (2019)
The development of higher education in the United States and abroad has been largely supported by private foundations (see Bacchetti & Ehrlich, 2006; Cheit & Lobman, 1979; Curti & Nash, 1965; Hollis, 1938; Sears, 1990). When it comes to funding innovative research around the world, U.S. foundations do have a strong track record. From the professionalisation of public health and the spread of Western medicine in many regions of the world to strengthening the non-governmental organisation (NGO) sector and many global research institutions, examples abound. Moreover, U.S. foundations’ interest in higher education is far from waning and has increased steadily as the Foundation Center’s data demonstrates. The total dollar value of grants made in this field is staggering: from 2003 to 2018, U.S. foundations made 1,075,821 grants to higher education for a total of USD 91.8 billion